2011
DOI: 10.1590/s1516-89132011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and evaluation of need for nitrogen fertilizer topdressing for maize leaf chlorophyll readings and the relationship with grain yield

Abstract: The study was carried out for two years in maize in succession to the wheat using no tillage system in a distroferric Red Latosol (Hapludox)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The application of 120 kg N ha -1 resulted in an increase of 22% and 15% in the chlorophyll levels compared to the not fertilized treatment with N, respectively, for the spring-summer and summer-fall seasons ( Figure 3A). Similarly, Silva et al (2011) reported that the N fertilizer topdressing resulted in an increase in the chlorophyll level of two maize cultivars. Maia et al (2013) applied 160 kg N ha -1 in topdressing and, also verified chlorophyll levels 13% higher in common bean cv.…”
Section: Inoculation Treatmentmentioning
confidence: 91%
“…The application of 120 kg N ha -1 resulted in an increase of 22% and 15% in the chlorophyll levels compared to the not fertilized treatment with N, respectively, for the spring-summer and summer-fall seasons ( Figure 3A). Similarly, Silva et al (2011) reported that the N fertilizer topdressing resulted in an increase in the chlorophyll level of two maize cultivars. Maia et al (2013) applied 160 kg N ha -1 in topdressing and, also verified chlorophyll levels 13% higher in common bean cv.…”
Section: Inoculation Treatmentmentioning
confidence: 91%
“…The GNDVI has been shown to be sensitive to plant chlorophyll concentrations, 89,90 which has been found to be directly related to end-of-season grain yields. 91,92 Previous studies have found that spectral data taken at flowering have produced the highest correlations with sorghum final grain yield, 45,73 which is why we chose to determine clusters with spectral data from this growth stage. Despite a trend of historical yield improvement for the hybrids used in this study, 93 hybrids in this study were not selected specifically for yield differences.…”
Section: Discussionmentioning
confidence: 99%
“…These results implied that, after enriched N at R1 growth stage, the shoot biomass increased more than that of root biomass. While at R1 growth stage, soybean demanded a plentiful nutritions and better canopy for photosynthesis, substance accumulation and material transportation 4,9,34 , the increased shoot biomass benefited for reproductive growth. Among three N treatments, the root/shoot rate of high yield cultivar was always lower than that of common yield cultivar, which implied that high yield cultivar have a strong root systems.…”
Section: Discussionmentioning
confidence: 99%
“…The N application affected the carbon metabolism and dry mass accumulation complicatly 8,3033 . N application at flowering stage influenced the reproductive growth and grain yield significantly 4,9,34 . It have been proved that applying N at R1 stage significantly increased the grain yield of two soybean cultivars with different yield potentials 35 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation